2013
DOI: 10.4209/aaqr.2011.11.0203
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics and Source Apportionment of Atmospheric Aerosol Particles in Kinmen-Xiamen Airshed

Abstract: The objective of this study was to characterize the chemical properties of atmospheric particles sampled in the KinmenXiamen Airshed located on the west bank of the Taiwan Strait. Seven particulate matter (PM) sampling sites in the KinmenXiamen Airshed, including three sites at Kinmen Island and four in urban Xiamen, were selected for this particular study. Regular sampling was conducted to collect PM 10 with high-volume samplers twice a month from March 2008, while intensive sampling was conducted to collect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
(41 reference statements)
2
26
0
1
Order By: Relevance
“…PM 10 was mainly transported from the coastal regions of China, Korean Peninsula, or Japan Islands toward the Penghu Islands . Previous studies reported that cyclonic air circulation was generally observed at the Xiamen Bay due to the topography of Bay Area, which inhibited the dispersion of PM 10 (Li et al, 2013a). Although both long-range transport and local emissions were the main causes for the accumulation of atmospheric particles at the Xiamen Bay, the contribution of local emissions was generally higher than that of long-rang transport.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…PM 10 was mainly transported from the coastal regions of China, Korean Peninsula, or Japan Islands toward the Penghu Islands . Previous studies reported that cyclonic air circulation was generally observed at the Xiamen Bay due to the topography of Bay Area, which inhibited the dispersion of PM 10 (Li et al, 2013a). Although both long-range transport and local emissions were the main causes for the accumulation of atmospheric particles at the Xiamen Bay, the contribution of local emissions was generally higher than that of long-rang transport.…”
Section: Introductionmentioning
confidence: 89%
“…The PM 10 concentrations were significantly increased at the southern Taiwan Strait. A superimposition phenomenon was regularly observed around the southern Taiwan Strait, which means local emissions and long-range transport were both important at the southern Taiwan Strait (Li et al, 2013a). Long-range transportation from northeastern coastal regions of North mainland China Korea Peninsula, and Japan Islands were significantly might affected the ambient atmospheric at northern than those at the southern Taiwan Strait.…”
Section: Spatiotemporal Variation Of Pm 10 Concentrationmentioning
confidence: 96%
“…(Park et al, 2011;Sahu et al, 2009). Kim et al, 2007; c) Kim et al, 2000; Zhou b) Li et al, 2013; c) Zhou et al, 2012; d) Zhao et al, 2013; Tan et al, 2009 석은 총 54일의 역궤적 분석일 중 객체 간 유사성이 …”
Section: Introductionunclassified
“…Many source apportionment studies have attempted to develop and implement air pollution control strategies for urban areas (Li et al, 2013a;Ni et al, 2013;Taiwo et al, 2016). Receptor models have been widely used to estimate the contribution from various types of sources, except for aeolian dust, to ambient air quality.…”
Section: Source Apportionment Of Pm 10 On Regular Days and During Andmentioning
confidence: 99%